Influence of friction stir processing parameters on surface modified 90Cu-10Ni composites. Issue 12 (10th September 2017) - Priyadharshini, G. Suganya; Subramanian, R.; Murugan, N.; Sathiskumar, R.
ABSTRACT: Friction Stir Processing (FSP) has emerged as a distinctive and pioneering solid state technique to produce surface composites. The objective of the present research is to produce reinforced 90/10 Copper–Nickel surface composites with different carbide-based ceramic particles through FSP and study the relationship of its dynamic parameters including tool rotational speed, tool traverse speed, and width of the groove over the surface behavior. Responses such as sliding wear, microhardness, and surface modified area in the friction stir processed region are modeled using polynomial, nonlinear, multiple regression based on the central composite design of experiment. Analysis of the developed models showed that the FSP parameters; traverse speed, rotational speed, and groove width have significant influence on both the sliding wear and microhardness of developed surface composite. And furthermore, tool rotational speed and tool traverse speed, simultaneously control dispersion of reinforcement in the surface. To validate the abovementioned noteworthy results and to study the microstructural aspects, selected specimens were carried over metallurgical analysis and the obtained results were put forward in detail in this paper.